Characteristics of fish fauna in marine ecosystems in the World Biosphere Reserve of Cu Lao Cham - Hoi An - Long, Nguyen Van; Dat, Mai Xuan (Vietnam Journal of Marine Science and Technology, 2020)
Assessments of fish fauna in the World Biosphere Reserve of Cu Lao Cham - Hoi An were based on analyses of data of visual censuses and samples collected at 5 sites of nipa palm, 9 sites of seagrass beds and 15 sites of coral reefs in June 2016, 200 samples from 25 fishing gears in wet and dry seasons (November 2015 and June 2016), and species composition gathered from previous (1994, 2004 and 2008) and recent studies (2017). A total of 356 species of 186 genera and 81 families of fishes were found in the waters of the Biosphere, in which some families were the most common including wrasses (Labridae: 42 species), damselfishes (Pomacentridae: 35), butterflyfishes (Chaetodontidae: 24), jack and travellies (Carangidae: 17), groupers (Serranidae: 14), surgeonfishes (Acanthuridae) and gobies (Gobiidae) with 11 species for each family, snappers (Lutjanidae: 10). The number of species in Cu Lao Cham waters (253 species) was 2.8 times higher than that in the Thu Bon estuary (91 species) and 4.2 times higher than that in transitional waters between the Thu Bon estuary and Cu Lao Cham (60 species). The coral reefs contributed 249 species and this was 8.6 times higher than that in the nipa palm (29 species), 6.5 times higher than in the seagrass beds (38 species) and 3.5 times higher than in the soft bottoms (71 species), however there were no significant differences between the nipa palm and the seagrass beds in the Thu Bon estuary. Among them, there were 10 valuable species of fishes found both in the Thu Bon estuary and Cu Lao Cham islands, and this indicates a high potential connectivity of these species among marine habitats in the two locations mentioned above